Rediscovering Relevance: The Key Role of Websites in Maintaining Radio Station Popularity - Harliantara, Harliantara (Dinasti Research, 2026)
In the age of algorithmic hegemony, traditional radio must contend with competition from music streaming services and independent podcasts. To survive and remain relevant, radio must conduct digital transformation by surfing on the wave of the Internet, and websites serve as the “anchor.” This study examines the extent to which websites promote and sustain radio stations. It focuses on three metropolitan stations in Indonesia: Sonora FM Jakarta, PRFM Bandung, and Suara Surabaya. Using a qualitative case study approach, data were collected with in-depth interviews with station managers, digital ethnography in a professional forum (FDR Indonesia), and content analysis of the stations’ digital properties. The study found that the website is not merely an option but a required “digital face” that enables a supportive symbiosis across platforms. By adding streaming radio, news archives, and podcasts on demand, stations turn passive audience members into active interactors. In conclusion, a radio station can best maintain its public and brand image by providing nonlinear material and hypermedia experience through a robust website